Students’ Perception of Online Mode of Facilitation at the Apapa Centre of the National Open University of Nigeria - Majebi, Enesi C.; Agbebaku, Henry U.; Adegbola, Eunice A.; Ume, Eucharia C.; Omuya, Sefinat O.; Okunade, Oluwasogo A (West African Journal of Open and Flexible Learning, 2023)
The National Open University of Nigeria (NOUN) adopted the online mode of facilitation among other resources to educate its over 100, 000 students. Students’ perceptions of the effectiveness of the online mode of facilitation at the NOUN could be multifaceted. This study employed a quantitative technique to examine the NOUN students’ perceptions of the efficiency of the institution’s online facilitation in meeting their educational expectations and to identify concerns that can have implications for appropriate intervention by the NOUN’s support system. Data were obtained from 80 students at the Apapa Study Centre of NOUN using questionnaire instruments. The questionnaires were administered through systematic random sampling techniques to some selected categories of students across the 72 programs of the 8 faculties of the University. Statistical tools (frequencies and percentages) were used to analyse and determine the students’ levels of awareness and effectiveness of the NOUN’s mode of online facilitation in enhancing their overall educational pursuits and online learning experiences. The study findings revealed that students’ experiences of the NOUN mode of online facilitation have enhanced their learning efficiency, which enables them to engage in their studies/research at their convenience time, study on their own, and enhance their proficiency in the use of computers and online learning experiences. Nonetheless, there is a need for the NOUN’s authorities to continually improve their support systems to enhance the opinions of a few students whose perceptions were relatively negative about the institution’s mode of online facilitation. Résumé : L’Université nationale ouverte du Nigeria (NOUN) a adopté le mode de facilitation en ligne, entre autres ressources, pour éduquer ses plus de 100 000 étudiants. Les perceptions des étudiants sur l’efficacité de ce mode de facilitation pourraient être diverses. Cette étude a utilisé une approche quantitative pour examiner les perceptions des étudiants de la NOUN quant à l’efficacité de la facilitation en ligne de l’institution pour répondre à leurs attentes éducatives et pour identifier les préoccupations ayant des implications pour une intervention appropriée du système de soutien de la NOUN. Les données ont été obtenues auprès de 80 étudiants du centre d’études d’Apapa de la NOUN à l’aide d’instruments de questionnaire. Les questionnaires ont été administrés par des techniques d’échantillonnage systématique aléatoire à certaines catégories sélectionnées d’étudiants dans les 72 programmes des 8 facultés de l’Université. Des outils statistiques (fréquences et pourcentages) ont été utilisés pour analyser et déterminer le niveau de conscience des étudiants et l’efficacité du mode de facilitation en ligne de la NOUN dans l’amélioration de leurs poursuites éducatives globales et de leurs expériences d’apprentissage en ligne. Les résultats de l’étude ont révélé que les expériences des étudiants avec le mode de facilitation en ligne de la NOUN ont amélioré leur efficacité d’apprentissage, leur permettant de s’engager dans leurs études/recherches à leur convenance, d’étudier de manière autonome et d’améliorer leur maîtrise de l’informatique et de l’apprentissage en ligne. Cependant, il est nécessaire que les autorités de la NOUN améliorent continuellement leurs systèmes de soutien pour renforcer les opinions de quelques étudiants dont les perceptions étaient relativement négatives à l’égard du mode de facilitation en ligne de l’institution. Mots-clés : Facilitation en ligne, perception des étudiants, apprentissage en ligne, systèmes de soutien aux étudiants.